Identification of Main Driving Factors of Water Resources Carrying Capacity in Taiyuan City - DING Xiangyi; SHI Xiaolin; WANG Xiangqian; MEI Chao (Renmin Zhujiang)
Utilizing the existing evaluation results of the water resources carrying capacity of Taiyuan City,this paper qualitatively analyzed its driving factors of the city,which was based on the analysis of the critical overload/overloading causes of various dimensions including quantity,quality,domain and flow and the consideration of the current situation of water resources in Taiyuan City.The paper also quantitatively identified the driving factors influencing the water resources carrying capacity of Taiyuan City with a combination weighting method of principal component analysis,analytic hierarchy process and entropy weight method.Further,making full use of the respective advantages of qualitative analysis and quantitative identification of driving factors,the paper took the common influencing factors as the main driving factors of the water resources carrying capacity of Taiyuan City.The results indicated that the main driving factors influencing the various dimensions of water resources carrying capacity in the city included the followings:①water quantity dimension:precipitation,per capita water resources,ratio of imported water to consumed water,groundwater extraction coefficient,coefficient of effective utilization of farmland irrigation water,water consumption per 10 000 yuan of industrial added value and wastewater utilization rate;②water quality dimension:water quality compliance rate of water function zone,proportion of water quality inferior to Grade V;③water domain dimension:soil erosion control rate;④water flow dimension:proportion of river ecological water replenishment.The research results can provide references for the plan formulation of improving water resources carrying capacity in Taiyuan City.